Internal polymeric coating materials for preventing pipeline hydrogen embrittlement and a theoretical model of hydrogen diffusion through coated steel. (26th August 2022) - Lei, Y.; Hosseini, E.; Liu, L.; Scholes, C.A.; Kentish, S.E.
Abstract: This work develops a theoretical analysis of the coating permeability necessary for use as internal coatings of transmission pipelines to prevent hydrogen embrittlement. Internal coating materials suitable to be applied in situ on existing steel pipelines are also evaluated. Twelve different commercially available coatings; crosslinked poly (vinyl alcohol) (PVA), poly (vinyl chloride) and bisphenol A diglycidyl ether (DGEBA)/polyetheramine (D-400) epoxy coatings prepared in-house were tested. Films fabricated from two commercial epoxies had hydrogen permeability of 0.40 Barrer and 0.35 Barrer respectively, which show potential as coating materials. A hydrogen permeability of 0.0084 Barrer was achieved with a crosslinked poly (vinyl alcohol) coating, indicating that this material shows the highest potential of all coatings tested. Unsteady-state hydrogen diffusion through coated steel was then modeled to evaluate the effect of the coating film in reducing hydrogen embrittlement. The result shows that with a 2 mm PVA coating, hydrogen permeation inside the coating will take seven years to reach equilibrium and the final hydrogen concentration on the steel surface will be 44% lower than that without a coating. Greater protection can be provided if coatings can be developed with lower hydrogen permeability. Highlights: Hydrogen permeability, solubility and diffusivity of 16 potential pipeline coatings were tested. All commercial coatings were too permeable to prevent hydrogen ingress. Crosslinked PVA films offered significantly lower hydrogen permeability. A 2 mm PVA coating could reduce the equilibrium hydrogen concentration on the steel surface by 44% after seven years.